Preoperative Liver Function Test Abnormalities Were Associated With Short-Term and Long-Term Prognosis in Cardiac Surgery Patients Without Liver Disease - Shang, Liqun; Ao, Yuanhan; Lv, Linhua; Lv, Lihua; Zhang, Yubi; Hou, Jian; Yao, Jianping; Wu, Zhongkai (Frontiers in Cardiovascular Medicine, 2021)
Aims: To explore the value of preoperative liver function tests (LFTs) for the prognosis of cardiac surgery patients without liver disease. Methods: The Medical Information Mart for Intensive Care III (MIMIC-III) database was used to extract the clinical data. Adult cardiac patients (≥18 years) without liver disease in the database were enrolled. The association of LFTs with time of hospital stay and ICU stay was analyzed with Spearman correlation. Survival curves were estimated using the Kaplan-Meier method and compared by the log-rank test. Multivariable logistic regression was used to identify LFTs that were independent prognostic factors of mortality. Results: A total of 2565 patients were enrolled in this study. ALB was negatively associated with the time of hospital stay and ICU stay, while ALT, AST and total bilirubin were positively associated with the time of hospital stay and ICU stay (all P <0.001). Abnormal ALB, ALT, AST and total bilirubin were associated with lower 90-day and 4-year survival (all P <0.001) and could be used as independent risk factors for hospital mortality and 90-day mortality . However, only ALB and total bilirubin were independent risk factors for 4-year mortality. Conclusion: Preoperative LFT abnormalities were associated with short-term and long-term prognosis of cardiac surgery patients without liver disease.